Фізико-механічні властивості композитів системи cBN-Al залежно від густини, фазового складу і структури - Беженар, М.П.; Лошак, М.Г.; Шульженко, О.О.; Коновал, С.М.; Александрова, Л.І.; Божко, С.А.; Нагорний, П.А.; Білявина, Н.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The relation between the density, the hardness, the fracture strength, the phase composition and the structure of composites of cBN-Al system (kiborit type) is studied. Effects of material test in the cutting tool are analyzed.